In-situ X-ray scattering study of isotactic polypropylene/graphene nanocomposites under shear during fused deposition modeling 3D printing. (18th August 2020) - Shmueli, Yuval; Lin, Yu-Chung; Zuo, Xianghao; Guo, Yichen; Lee, Sungsik; Freychet, Guillaume; Zhernenkov, Mikhail; Kim, Taejin; Tannenbaum, Rina; Marom, Gad; Gersappe, Dilip; Rafailovich, Miriam H.
Abstract: Complementary techniques were applied to characterize the structure property relationships of FDM printed isotactic polypropylene/graphene nanocomposites. Raman spectroscopy indicated that graphene was mostly exfoliated during the nozzle extrusion process. Rheological measurements of the viscosity indicated that the presence of graphene induced shear thinning during extrusion. Azimuthal scans of wide angle x-ray scattering indicate correlated thermal fluctuations of the graphene platelets which stops abruptly at the onset of transcrystallization, or templating of the iPP chains on the graphene. X-ray microbeam SAXS analysis show the formation of 'shish-kebab' structures at the core of the unfilled filaments, where the 'kebab' component vanishes at the fiber-fiber interface enabling interdiffusion. Weak lamellar structure, and a corresponding decrease in the storage modulus are observed with the addition of 5% graphene. The lamellar structure disappears entirely with the addition of 10% graphene, while the storage modulus is decreased by nearly 50%. Thermal imaging of heat flux dissipation across molded and printed samples shows no orientational effects in pure iPP despite differences in crystal structure. Thermal conductivity increases dramatically in the samples with 10% graphene, and strong orientational effects are observed where the thermal coefficients differ by 180% between samples printed parallel or perpendicular to the heat flux.